2022
DOI: 10.1371/journal.pone.0263586
|View full text |Cite
|
Sign up to set email alerts
|

Antibody microarray analysis of amniotic fluid proteomes in women with cervical insufficiency and short cervix, and their association with pregnancy latency length

Abstract: Introduction This study aimed to investigate amniotic fluid (AF) proteins that were differentially expressed between patients with cervical insufficiency (CI) and asymptomatic short cervix (SCX, ≤ 25 mm), and whether these proteins could be predictive of spontaneous preterm birth (SPTB) in these patients. Method This was a retrospective cohort study of 129 singleton pregnant women with CI (n = 80) or SCX (n = 49) at 17 to 26 weeks who underwent amniocentesis. An antibody microarray was used to perform compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 66 publications
(69 reference statements)
2
4
0
Order By: Relevance
“…27,32,33 In the context of PTL, cervical insufficiency, and a short cervix, a recent study from our group have demonstrated that EN-RAGE levels are significantly increased in the AF of women with spontaneous preterm delivery (SPTD) compared with controls. 34,35 Overall, these data are consistent with the current results of AF EN-RAGE based on ELISA assay, considering previous studies that reported significant associations of acute HCA with SPTD/MIAC/IAI risk in the PPROM setting. 24,36 TNFR2 is a transmembrane receptor that can bind to tumor necrosis factor (TNF)-α, a pleiotropic cytokine that plays critical roles in host defense and acute/chronic inflammation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…27,32,33 In the context of PTL, cervical insufficiency, and a short cervix, a recent study from our group have demonstrated that EN-RAGE levels are significantly increased in the AF of women with spontaneous preterm delivery (SPTD) compared with controls. 34,35 Overall, these data are consistent with the current results of AF EN-RAGE based on ELISA assay, considering previous studies that reported significant associations of acute HCA with SPTD/MIAC/IAI risk in the PPROM setting. 24,36 TNFR2 is a transmembrane receptor that can bind to tumor necrosis factor (TNF)-α, a pleiotropic cytokine that plays critical roles in host defense and acute/chronic inflammation.…”
Section: Discussionsupporting
confidence: 91%
“…In previous proteomic studies of AF samples using surface‐enhanced laser desorption/ionization mass spectrometry, EN‐RAGE levels were found to be elevated in the AF of PPROM or preterm labor (PTL) patients with HCA, MIAC, and IAI compared with those without these conditions 27,32,33 . In the context of PTL, cervical insufficiency, and a short cervix, a recent study from our group have demonstrated that EN‐RAGE levels are significantly increased in the AF of women with spontaneous preterm delivery (SPTD) compared with controls 34,35 . Overall, these data are consistent with the current results of AF EN‐RAGE based on ELISA assay, considering previous studies that reported significant associations of acute HCA with SPTD/MIAC/IAI risk in the PPROM setting 24,36 …”
Section: Discussionmentioning
confidence: 64%
“…65,66 In our previous study, we demonstrated that increased uPA levels in the AF were independently associated with SPTB development in women with acute cervical insufficiency. 67 These findings and biological functions of uPA are not only generally consistent with but also support the present findings concerning the relationships between uPA levels in the AF and the risks of IAI/MIAC and SPTB in women with PTL. This is because preterm parturition syndrome may exhibit phenotypes, such as PTL, cervical insufficiency, and PPROM, 68 and is associated with inflammatory/infectious processes.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, TNFα and LPS enhance the release of uPA under in vitro conditions and in animal studies 65,66 . In our previous study, we demonstrated that increased uPA levels in the AF were independently associated with SPTB development in women with acute cervical insufficiency 67 . These findings and biological functions of uPA are not only generally consistent with but also support the present findings concerning the relationships between uPA levels in the AF and the risks of IAI/MIAC and SPTB in women with PTL.…”
Section: Discussionmentioning
confidence: 89%
“…8,9,12,50 However, few or no studies have investigated the predictive value of AF EN-RAGE for subsequent SPTB risk after rescue cerclage while reporting on its reliable predictive capability in patients with acute CI or those with a short cervix, regardless of cerclage. 51 In the context of rescue cerclage for acute CI, our study showed for the first time that high AF EN-RAGE levels were associated with a higher proportion of individuals delivering preterm at < 32 weeks, as well as a shorter median duration of gestational latency. EN-RAGE (also known as S100A12 or calgranulin C) plays a crucial role in the regulation of inflammatory processes and immune responses by binding to receptors for advanced glycation end products.…”
Section: Discussionmentioning
confidence: 61%